Does exchange-rate uncertainty matter in the Malaysia–E.U. bilateral trade? An industry level investigation - Aftab, M.; Ahmad, R.; Ismail, I.; Ahmed, M. (Kluwer (now part of Springer), 2016)
Due to ambiguity in the past literature, researchers have examined exchange rate volatility effect on trade using disaggregated data in recent years. Previous research has focused more on aggregated data having aggregation bias which has led to unnecessarily over-generalized findings. This study investigates the impact of exchange rate volatility on the Malaysian bilateral trade flows with European Union using industry level data. Our empirical findings, based on auto-regressive distributed lag framework, suggest that many import and export industries experience exchange rate volatility influence in the short run, while a very small number of industries show this effect in the long run. Moreover, the adverse impact of financial crisis (2007–2008) is more prevalent on import industries compared to export industries.